PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DAN PROJECT BASED LEARNING (PjBL) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Zakiyah, Luluk; Supandi, Supandi; Dwijayanti, Ida (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2023)
ABSTRACT. This study aims to determine the effect of Problem Based Learning (PBL) and Project Based Learning (PjBL) Learning Models on Students' Mathematical Communication Ability. The population in this study were all 8th grade students of SMP Negeri 1 Sukorejo in the 2021/2022 academic year. Samples were taken randomly as many as 3 classes, namely class A, B and D as the control class and the experimental class with simple random sampling technique. The research design used is Posttest-Only Control Design. The data collection used in this research is by observing, documenting, and giving written tests. The results of this study state that (1) There are differences in students' mathematical communication skills in learning mathematics using Problem Based Learning (PBL), Project Based Learning (PjBL) and conventional models. (2) Students' mathematical communication skills in Problem Based Learning (PBL) learning models are better than conventional learning models. (3) Students' mathematical communication skills in the Project Based Learning (PjBL) learning model are better than the conventional learning model. (4) There is no difference in students' mathematical communication skills in the Project Based Learning (PjBL) and Problem Based Learning (PBL) models.Keywords: Effect, Problem Based Learning, Project Based Learning, Mathematical Communication ABSTRAK. Penelitian ini bertujuan untuk mengetahui pengaruh Model Pembelajaran Problem Based Learning (PBL) Dan Project Based Learning (PjBL) Terhadap Kemampuan Komunikasi Matematis Siswa. Populasi pada penelitian ini adalah seluruh siswa kelas VIII SMP Negeri 1 Sukorejo tahun ajaran 2021/2022 sebanyak 8 kelas. Sampel diambil secara random sebanyak 3 kelas yaitu kelas A, B dan D sebagai kelas kontrol dan kelas eksperimen dengan teknik simple random sampling. Desain penelitian yang digunakan adalah Posttest-Only Control Design. Pengumpulan data yang digunakan dalam penelitian ini adalah dengan melakukan observasi, dokumentasi, dan pemberian tes tertulis. Hasil penelitian ini menyatakan bahwa (1) Terdapat perbedaan kemampuan komunikasi matematis siswa pada pembelajaran matematika yang menggunakan model Problem Based Learning (PBL), Project Based Learning (PjBL) dan konvensional. (2) Kemampuan komunikasi matematis siswa pada model pembelajaran Problem Based Learning (PBL) lebih baik dari pada model pembelajaran konvesional. (3) Kemampuan komunikasi matematis siswa pada model pembelajaran Project Based Learning (PjBL) lebih baik dari pada model pembelajaran konvesional. (4) Tidak terdapat perbedaan kemampuan komunikasi matematis peserta didik pada model pembelajaran Project Based Learning (PjBL) dan model Problem Based Learning (PBL).Kata Kunci: Pengaruh, Problem Based Learning, Project Based Learning, Komunikasi Matematis